Pengaruh Kompetensi Pegawai Terhadap Kualitas Pelayanan Pembayaran Pajak Kendaraan Bermotor Roda Dua Di Kantor Sistem Administrasi Manunggal Satu Atap Kota Palu. - Hikmah, Nurul; Susanti, Ani; Salingkat, Syarif Permana (JPS: Journal of Publicness Studies, 2024)
This study was conducted with the aim of determining the Influence of Employee Competence on the Quality of Motor Vehicle Tax Payment Services at the Palu City One-Stop Manunggal System Office. This study uses quantitative research conducted based on numbers and analyzed statistically. By using Edison et al's theory for competency variables with 3 dimensions, namely, knowledge, expertise, and attitude, and on service quality using Dwiyanto's theory with 5 dimensions, namely, attitude, procedure, time, facilities, and service costs. The data collection technique carried out in this study is by distributing questionnaires and surveys which are analyzed by quantitative descriptive analysis methods. The population of this study is all taxpayers who pay motor vehicle tax at the Palu City Samsat Office which amounted to 46,354 taxpayers, the sample drawing technique in this study uses the Slovin Formula with the number of samples obtained as many as 99.78 which is rounded to 100 respondents. Based on the results of this study, it was shown that the results of the normality test met the assumption of normality or Asymp.Sig (2 – tailed) of 0.076 > 0.05. The results of a simple linear regression analysis show that the competency variable has a significant influence on service quality with the regression equation Y = 6.518 + 0.764X. With the results of the F test on the F value of the F calculation > the table or 113.107 > 3.94, therefore it can be stated that the competence of employees has a simultaneous effect on the quality of service by paying taxes on two-wheeled motor vehicles at the Palu City Samsat Office. In addition, the value of the determination coefficient is 0.536 which shows that 53.6% of the service quality variable can be explained by the employee competency variable, while the remaining 46.4% is influenced by other factors. And the results of the hypothesis test stated that the competence of employees affects the quality of Samsat Kota services.